The legal requirements for the proclamation of Air Defence Identification Zones (ADIZ) : an examination with specific reference to the ADIZ of the Peoples Republic of China - Hobe, Stephan (University of Pretoria, 2016)
Mini Dissertation (LLM)--University of Pretoria, 2015.